Atmospheric impacts of chlorinated very short-lived substances over the recent past – Part 2: Impacts on ozone - Bednarz, Ewa M.; Hossaini, Ryan; Chipperfield, Martyn P. (2023)
Depletion of the stratospheric ozone layer remains an ongoing environmental issue, with increasing stratospheric chlorine from Very Short-Lived Substances (VSLS) recently emerging as a potential but uncertain threat to its future recovery. Here the impact of chlorinated VSLS on past ozone is quantified, for the first time. using the UM-UKCA chemistry-climate model. Model simulations show that between 2010–2019 Cl-VSLS reduced total column ozone by, on average, ~2–3 DU in the springtime high latitudes and by ~0.5–1 DU in the tropics, with up to 5–6 DU monthly and zonal mean Arctic ozone reductions simulated in the springs of 2011, 2014 and 2020. Cl-VSLS impacts during the recent cold Arctic winter of 2019/2020 are also quantified to have resulted in up to 6 % reduction of lower stratospheric ozone and ~6 DU ozone in total by the end of March. On the other hand, the simulations show that the inclusion of Cl-VSLS does not considerably modify the magnitude of the diagnosed recent ozone trends. We also estimate the ozone depletion potential of dichloromethane, the most abundant Cl-VSLS, at 0.0107. Our results thus illustrate a so-far modest but nonetheless non-negligible role of Cl-VSLS in contributing to stratospheric ozone budget over the recent past that if to continue could offset some of the gains achieved by the Montreal Protocol.